Influence of seed storage conditions and germination media on the germination of a priority bamboo species, Dendrocalamus brandisii (Munro) Kurz - Lakshmi, C.J.; Seethalakshmi, K.K.; Jijeesh, C. M. (Journal of Tropical Agriculture, 2019)
The present investigation was formulated to determine the optimum storage condition and suitable germination media for enhancing the germination of Dendrocalamus brandisii seeds. Seed samples were stored at 4oC, 16oC and room temperature. The influence of four media on germination of the seeds was also estimated. Of the four media used, higher germination rates were observed in the vermiculite (60%), followed by quartz sand (55%), germination paper (55%) and soil (36%). Seeds with initial germination of 60 %, when stored for 36 months at 4oC and 45% relative humidity (RH) maintained their viability throughout the storage period. Whereas, in room temperature and 16oC, the seeds were viable only up to five and ten months respectively. The results indicated that seed viability of D. brandisii could be extended by reducing moisture content up to a critical level (8%) prior to storage, and fluctuations in moisture content play a significant role in seed deterioration and decrease in seed germination. It was also found that speed of germination was higher in vermiculite and germination paper (0.62) and lower in soil (0.22). Peak value was highest in germination paper (4.62), followed by vermiculite (3.76). Higher germination value was for vermiculite (0.27), followed by quartz sand and germination paper (0.16). The findings will contribute for successful storage of seeds, whenever flowering and seed set occurs and will help to establish plantations using seedlings.